PENGARUH PEMANFAATAN TEKNOLOGI INFORMASI, KESESUAIAN TUGAS, DAN EFEKTIVITAS SIA TERHADAP KINERJA KARYAWAN PADA KOPDIT TRI TUNGGAL TUKA - Alexsdipa, Agustinus I Ketut; Dwiana Putra, I Made Pande (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.11.NO.01.TAHUN.2022DO - 10.24843/EEB.2022.v11.i01.p03, 2022)
The development of technology-based information systems requires companies and organizations to make changes in the information sector so that they do not lag behind in absorbing information. Accounting is a tool in managing accounting and financial data, so an information system is needed to be able to convey this information to those in need, namely the accounting information system. This study aims to obtain empirical evidence of the effect of Information Technology Utilization, Task Suitability, and Effectiveness of Accounting Information Systems on Employee Performance at the Tri Tunggal Tuka Credit Cooperative. The sampling method used in this research is the saturated sampling technique, where the saturated sampling technique is used as the sample. Data collection methods used in this study were questionnaires and interviews. The data analysis techniques in this study are Descriptive Statistical Analysis, Classical Assumption Test, Multiple Linear Regression Analysis, Model Feasibility Test (F Test), Hypothesis Test (t Test), and Coefficient of Determination Test (R^2). The results in the study concluded that the use of information technology, task suitability, and the effectiveness of accounting information systems had a positive effect on employee performance of the Tri Tunggal Tuka Credit Cooperative.